2018
DOI: 10.17511/ijphr.2018.i2.08
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of dog bite cases in a rural area of Salem, Tamil Nadu

Abstract: Introduction:Rabies is a viral zoonosis. In up to 99% of cases, domestic dogs are responsible for rabies virus transmission to humans. About 30% of the victims of dog bites are children under the age of 15. Objective: To assess the epidemiological pattern of dog bite cases, which formed the majority of cases attending anti-rabies clinic. Materials and Methods: This study was conducted at the Primary Health Centre,Poolavari, Salem, Tamil Nadu, India between Feb 1st-May 1 st 2018. It is a cross sectional study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 5 publications
3
10
0
Order By: Relevance
“…Only one modeling study reported all the three outcomes: epidemiological, economic and humanistic. 1 Out of 35 included studies, 23 were hospital (or clinic) based, [20][21][22][24][25][26][27][28][29][30][31]38,41,42,[44][45][46][47][48][49][50][51][52] 9 were community (or household) based 4,23,[32][33][34][35]37,39,40 and 2 were modeling studies at country level 1,43 and was laboratory-based study. 36…”
Section: Search and Screeningmentioning
confidence: 99%
See 4 more Smart Citations
“…Only one modeling study reported all the three outcomes: epidemiological, economic and humanistic. 1 Out of 35 included studies, 23 were hospital (or clinic) based, [20][21][22][24][25][26][27][28][29][30][31]38,41,42,[44][45][46][47][48][49][50][51][52] 9 were community (or household) based 4,23,[32][33][34][35]37,39,40 and 2 were modeling studies at country level 1,43 and was laboratory-based study. 36…”
Section: Search and Screeningmentioning
confidence: 99%
“…The cohort studies included for epidemiological outcomes failed to describe any efforts to address potential sources of bias, statistical methods, other analyses undertaken and their external validity. [40][41][42] The criteria that were not reported in cross-sectional studies included for epidemiological outcomes were bias (95.2%), 4,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] other analyses (76.2%), [20][21][22][23][24][25][26][27][28][29][30]32,[35][36][37][38] generalisability (71.4%), [20][21][22][23][24][26][27][28][30][31]…”
Section: Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations